PENGUKURAN CAPABILITY LEVEL LAYANAN SIAKAD UIN MENGGUNAKAN FRAMEWORK COBIT 5 - Rachmah Agus Putri; Nanda Kurnia Wardati; Sharfina Febbi Handayani (LP3M Universitas Putra Bangsa, 2024)
The research pursues the measurement of the capability level of UIN’s SIAKAD services using the COBIT 5 framework, focusing on the EDM04, APO01, APO07, BAI08, and DSS01 domains. The selected domain is based on the mapping between organization, IT Goals, and COBIT 5 processes. The measurement was carried out to evaluate the SIAKAD services aligned with the COBIT 5 standards. The data collection is carried out through interviews based on the RACI chart, best practice COBIT 5 questionnaires, and evidence. The measurement results show gaps between the current level and the expected level. The capability level for EDM04 is at Level 1, APO01 at Level 1.6, APO07 at Level 1, BAI08 at Level 1.5, and DSS01 at Level 1. The target levels to be achieved are Level 2 and Level 3. This research’s findings are expected to support IT service in improving IT governance to achieve the strategic objectives of SIAKAD services.